The Effect of Focus Instructions on Dart Throwing Performance in Children With and Without Developmental Coordination Disorder - Shabnam Fathi Khatab; Abdollah Ghasemi; Seyed Kazem Mousavi Sadati (The Society of Aging and Physical Activity (SAPA), 2018)
Background. Adults benefit more from an external focus than internal focus when performing motor skills. Objectives. The aim of this study was to investigate the effects of internal and external focus of attention on dart throwing performance in children with and without developmental coordination disorder. Methods. Twenty men, 20 normal boys and 20 boys with developmental coordination disorder were selected by Motor Observation Questionnaire for Teachers. The task was to throw the darts to the target which was performed in two experimental conditions including internal (related to the movements of the fingers and arm) and external (related to target and dart's course) focus of attention. Results. The results of ANOVA with repeated measures indicated that along with Constrained Action Hypothesis, adults performed better in the condition of external focus of attention. However, for normal children, the use of the internal focus of attention was more effective and in children with developmental coordination disorder, no significant difference between the two conditions was found. Conclusion. According to results of this study, therapists and coaches should adjust their methods and instructions based on age, experience and developmental conditions of individuals.